Epidemiological characteristics of foodborne disease outbreaks in Chongqing from 2003 to 2023 - Jingrong Chen; Qing Liu; Shuquan Luo; Yuan He; Li Cheng; Ping Feng; Fang Li; Wenming Jiang (PLoS ONE, 2026)
Foodborne diseases have a high incidence and widespread occurrence, affecting a significant number of individuals, making them one of the most pressing public health issues globally. The situation regarding foodborne diseases in China is similarly concerning. This study collected data on foodborne disease outbreaks reported by 39 districts and counties in Chongqing from 2003 to 2023 and analyzed the epidemiological characteristics. The aim was to understand the patterns and trends of foodborne disease outbreaks in Chongqing, thereby providing a scientific basis for developing effective prevention and control strategies. From 2003 to 2023, a total of 767 foodborne disease outbreaks were reported in Chongqing, resulting in 10,462 individual cases and 43 fatalities. Domestic settings were identified as the primary location for these incidents, accounting for 46.4% (356/767) of the total occurrences, followed by hotel and restaurant, which contributed 25.0% (192/767). The majority of incidents occurred between May and October. The highest number of incidents was associated with the consumption of poisonous mushrooms, totaling 204 cases, which represents 26.6% (204/767) of all reported incidents. This was followed by meat and meat products, which accounted for 94 incidents, or 12.3% (94/767). Poisonous mushrooms and aconitines emerged as the leading pathogenic factors contributing to fatalities, responsible for 27.9% (12/43) and 16.3% (7/43) of the total deaths, respectively. In recent years, the epidemiological characteristics of foodborne disease outbreaks in the region have evolved. Since 2020, surveillance datum has indicated that mushroom-related events have emerged as the predominant cause of both foodborne disease incidents and associated fatalities in Chongqing. It is essential to enhance monitoring of cases and incidents, improve incident response and early warning mechanisms, conduct comprehensive analyses of the factors contributing to the high incidence of these events, and implement targeted supervision and education for critical locations, pathogenic factors, and personnel.